Monocyte subsets and their phenotypes during treatment with BCR‐ABL1 tyrosine kinase inhibitors for Philadelphia chromosome‐positive leukemia - Konuma, Takaaki; Kohara, Chisato; Watanabe, Eri; Mizukami, Motoko; Nagai, Etsuko; Tanoue, Susumu; Isobe, Masamichi; Jimbo, Koji; Kato, Seiko; Ohno, Nobuhiro; Takahashi, Satoshi; Tojo, Arinobu (Hematological oncology, 2018)
BCR‐ABL1 tyrosine kinase inhibitors (TKIs) are effective agents in the treatment of Philadelphia chromosome‐positive leukemia. However, vascular events have developed in some patients receiving each TKI. The perturbation of circulating monocyte subsets and their expressions of chemokine and scavenger receptors are associated with the development of cardiovascular events. Here, we examined the subsets of circulating monocytes and their phenotypes in 51 patients treated with imatinib, nilotinib, and dasatinib, and 11 healthy subjects in our institute. Except for a negative association between the number of classical monocytes and imatinib treatment, the proportions and numbers of monocyte subsets were not significantly associated with TKI treatment. However, chemokine receptors, CCR2, CX3CR1 on classical monocytes, and scavenger receptor, CD204, on intermediate and non‐classical monocytes were significantly associated with TKIs. These data demonstrated the relationships between alterations of chemokine and scavenger receptors on different monocyte subsets and the TKI treatments.